Australian Socially Responsible Funds: Performance, Risk and ScreeningIntensity - Humphrey, Jacquelyn E.; Lee, Darren D. (2011)
We investigate the performance and risk of Socially Responsible Investment (SRI) equity funds in the Australian market and find no significant difference between the returns of SRI and conventional funds. In an extension to prior literature, we examine the impact of the number of positive, negative and total screens funds impose on performance and risk. We find little evidence of positive or negative screening impacting total return, but find weak evidence that funds with more screens overall provide better risk-adjusted performance. Positive screening significantly reduces funds’ risk. However, negative screening significantly increases risk and reduces funds’ abilities to form diversified portfolios.
Keywords: Australia; mutual funds; SRI funds; Socially Responsible Investment